2A) a+b=12,5 a=4b 4b+b=12,5 b=12,5/5=2,5 a=12,5-2,5=10
2B) a-b=40,5 b=a/4 a=4b 4b-b=40,5 b=40,5/3=13,5 a=40,5+13,5=54
3A) a+b+c=72,45 b=a+1,2 c=a-1,2 a+a+1,2+a-1,2=72,45
a=72,45/3=24,15 b=24,15+1,2=25,35 c=24,15-1,2=22,95
3B) a+b+c=18,5 a=b/3 c=b+1 b/3+b+b+1=18,5 (x3)
b+3b+3b+3=55,5 7b=52,5 b=7,5 a=7,5/3=2,5 c=7,5+1=8,5
3C) a+b+c=18,8 b=a+5 a=c/2 c/2+ c/2 +5 +c=18,8 (x2)
c+c+10+2c=37,6 4c=36,6 c=9,15 a=4,575 b=9,575
3D) a=b/2=c/3 c-b=2,5 c=b+2,5 a=b/2=(b+2,5)/3
3b=2(b+2,5) 3b=2b+5 b=5 c=7,5 a=2,5